Evolution of an Amazonian Fish Is Driven by Allopatric Divergence Rather Than Ecological Divergence - Leroux, Nicolas; Sylvain, François-Étienne; Normandeau, Eric; Holland, Aleicia; Val, Adalberto Luis; Derome, Nicolas (Frontiers in Ecology and Evolution, 2022)
Lowland central Amazonia is characterized by heterogeneous riverscapes dominated by two chemically divergent water types: black (ion-poor, rich in dissolved organic carbonate and acidic) and white (rich in nutrient and turbid) waters. Recent phylogeographic and genomic studies have associated the ecotone formed by these environments to an ecologically driven genetic divergence between fish present in both water types. With the objective of better understanding the evolutionary forces behind the central Amazonian Teleostean diversification, we sampled 240 Mesonauta festivus from 12 sites on a wide area of the Amazonian basin. These sites included three confluences of black and white water environments to seek for repeated evidences of ecological divergence at the junction of these ecotones. Results obtained through our genetic assessment based on 41,268 SNPs contrast with previous findings and support a low influence of diverging water physicochemical characteristics on the genetic structuration of M. festivus populations. Conversely, we detected patterns of isolation by downstream water current and evidence of past events of vicariance potentially linked to the Amazon River formation. Using a combination of population genetics, phylogeographic analysis and environmental association models, we decomposed the spatial and environmental genetic variances to assess which evolutionary forces shaped inter-population differences in M. festivus’ genome. Our sampling design, comprising three confluences of black and white water rivers, supports the main role of evolution by allopatry. While an ecologically driven evolution admittedly played a role in Amazonian fish diversification, we argue that neutral evolutionary processes explain most of the divergence between M. festivus populations.